Can Open Source projects succeed when the producers are not users? Lessons from the data processing field - Jullien, Nicolas; Roudaut, Karine (Management international / International Management / Gestiòn Internacional, 2012)
Free/Libre Open Source Software (FLOSS) proposes an original way to solve the incentive dilemma for the production of information goods, based on von Hippel (1988)’s user-as-innovator principle: as users benefit from innovation, they have incentive to produce it, and as they can expect cumulative innovation on their own proposition, they have incentive to share it. But what is the incentive for producers when they are not users? We discuss this question via a qualitative study of FLOSS projects in “algorithm-based industries”. We find that in this case producers hardly participate in such projects.